Fundamental roles of the Optineurin gene in the molecular pathology of Amyotrophic Lateral Sclerosis - Shumin Zhao; Shumin Zhao; Ranran Chen; Ranran Chen; Ying Gao; Ying Gao; Yanchao Lu; Yanchao Lu; Xue Bai; Xue Bai; Jingjing Zhang; Jingjing Zhang (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the progressive loss of motor neurons (MNs) in the brain and spinal cord. It is caused by multiple factors, including mutations in any one of several specific genes. Optineurin (OPTN) mutation is an essential cause of some familial and sporadic ALS. Besides, as a multifunctional protein, OPTN is highly expressed and conserved in the central nervous system. OPTN exerts its functions by interacting with various proteins, often acting as an adaptor to provide a link between two or more core proteins related to autophagy and inflammation, etc. OPTN mutation mainly results in its function deficiency, which alters these interactions, leading to functional impairment in many processes. Meanwhile, OPTN immunopositive inclusions are also confirmed in the cases of ALS due to C9ORF72, FUS, TARDBP, and SOD1 mutations. Therefore, OPTN gene may play fundamental roles in the molecular pathology of ALS in addition to OPTN mutation. In this review, we summarize the recent advances in the ALS pathology of OPTN defect, such as mitophagy disorder, neuroinflammation, neuronal axonal degeneration, vesicular transport dysfunction, etc., which will provide a reference for research on the pathogenesis and treatment of ALS.